CHOLESTEROL-LOWERING PROPERTY OF BACILLUS CEREUS STRAIN KAVK4 ISOLATED FROM BUTTER - K, Amutha; V, Kokila (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The aim of the present study was to check the cholesterol-lowering property of Bacillus cereus strain KAVK4 at different concentration of cholesterol, different pH, different temperature, and different incubation time. Methods: B. cereus strain KAVK4 was isolated from butter by spread plate method. The cholesterol-lowering property was studied by adding different concentration of cholesterol in nutrient agar medium. Further, the cholesterol-lowering ability was optimized at various parameters such as different concentration of cholesterol, different pH, different temperature, and different incubation time. Results: B. cereus strain KAVK4 was utilized cholesterol and grown well in nutrient medium containing cholesterol at 1 mg/ml concentration. The cholesterol utilization was optimized at 1 mg/ml concentration, the optimal pH was at 8, the temperature at 30Â°C, and the incubation period was at 24 hrs. Conclusion: B. cereus strain KAVK4 was able to utilize cholesterol from the culture medium. Hence, B. cereus strain KAVK4 has been reported as cholesterol lowering agent. Keywords: Cholesterol lowering, Bacillus cereus, pH, Temperature, Time.